The Importance of Neutrophil-to-Lymphocyte Ratio in Chronic Obstructive Pulmonary Disease - In, Erdal; Kuluozturk, Mutlu; Oner, Tnsel; Deveci, Figen (Bilimsel Tip Publishing House, 2016)
OBJECTIVES: Chronic obstructive pulmonary disease (COPD) is a common lung disease characterized by airflow limitation and systemic inflammation. Recently, neutrophil-to-lymphocyte ratio (NLR) has gathered increasing interest in the detection of inflammation in inflammatory diseases. This study aimed to investigate the role of NLR in COPD for identifying the detection of inflammation and recognition of acute exacerbation. MATERIAL AND METHODS: The laboratory results of 103 COPD patients were included into the study, of which 47 patients were in acute exacerbation and 56 patients were at stable period, and there were 40 gender and age-matched healthy controls. Complete blood count (CBC), C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) were evaluated. NLR was calculated from CBC. RESULTS: NLR values of patients with COPD (both acutely exacerbated and stable) were found significantly higher than those of the controls (p<0.001, p<0.05; respectively). In all patients with COPD, NLR values positively correlated with serum CRP (r=0.641, p<0.001) and ESR (r=0.276, p=0.005) levels and negatively correlated with forced vital capacity (r=-0.20,p=0.043) and forced expiratory volume in the 1st second (r=-0.288, p=0.003). For an NLR cutoff of 3.34, sensitivity for detecting exacerbation of COPD was 78.7% and specificity was 73.2% (AUC 0.863, p<0.001). CONCLUSION: Our results suggest that NLR may be considered as a reliable and simple indicator in the determination of increased inflammation in patients with COPD. Furthermore, NLR could be useful for the early detection of possible acute exacerbations in patients with COPD.
Keywords: Chronic obstructive pulmonary disease; neutrophil-to-lymphocyte ratio; inflammation